2022
DOI: 10.1785/0220210288
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Time Warping as an Alternative to Windowed Cross Correlation in Seismological Applications

Abstract: We investigate the feasibility of using the dynamic time warping (DTW) technique as an alternative to windowed cross correlation (WCC) for an indirect measure to quantify both the similarity and relationship between two seismic time series. We first examine the sensitivity and performance of the DTW technique by analyzing both synthetic and real seismic time series in geophysical applications. Results show that DTW efficiently retrieves useful information from seismic data and has a high sensitivity to minor v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 86 publications
0
4
0
Order By: Relevance
“…The signals are analyzed and compared using Pearson correlation, dynamic time warping (DTW), and time-frequency representation. Phantom 1, for instance, has a normalized DTW distance of 0.13 and a Pearson correlation coefficient of 0.99, which indicates that the two signals are reasonably well-matched Girault, Kouame, Ouahabi and Patat (2000); Niethammer, Jacobs, Qu and Jarzynski (2001); Kumar, Legendre, Zhao and Chao (2022); Bhardwaj and Maini (2022). According to an examination of the PIP data, gelatin percentage and 𝜂1 in the first layer have a positive relationship, as increasing gelatin percentage causes an increase in 𝜂1 value Nguyen et al (2014); Ismail et al (2017).…”
Section: Discussionmentioning
confidence: 99%
“…The signals are analyzed and compared using Pearson correlation, dynamic time warping (DTW), and time-frequency representation. Phantom 1, for instance, has a normalized DTW distance of 0.13 and a Pearson correlation coefficient of 0.99, which indicates that the two signals are reasonably well-matched Girault, Kouame, Ouahabi and Patat (2000); Niethammer, Jacobs, Qu and Jarzynski (2001); Kumar, Legendre, Zhao and Chao (2022); Bhardwaj and Maini (2022). According to an examination of the PIP data, gelatin percentage and 𝜂1 in the first layer have a positive relationship, as increasing gelatin percentage causes an increase in 𝜂1 value Nguyen et al (2014); Ismail et al (2017).…”
Section: Discussionmentioning
confidence: 99%
“…We have tested the accuracy of this approach using synthetic waveform datasets with waveforms of different lengths. Recent studies have shown that in many cases, DTW, which has a higher computational cost, is a superior distance metric for time series clustering when compared to cross-correlation or direct distance measures between unstretched waveforms ( 42 ).…”
Section: Methodsmentioning
confidence: 99%
“…Ganter et al (2018) proposed a similar waveform search based on ML to generate templates satisfying the alternate null hypothesis, which incorporates the possibility of false positives. Kumar et al (2022) suggested that using the dynamic time warping technique instead of cross-correlations possibly improves the performance of similar waveform searching, including template matching analysis and unsupervised waveform clustering.…”
Section: Similar Waveform Searchingmentioning
confidence: 99%